SÍNTESE E CARACTERIZAÇÃO DE DÍADES VISANDO A APLICAÇÃO EM DISPOSITIVOS FOTOVOLTAICOS - Becher, Tiago Branco (2013)
In this paper we address the development of synthetic routes to four organic structures called dyads, which are compounds formed by an electron donating group covalently attached to an electron acceptor group. What sparked your interest in synthesizing these molecules was the potential of being applied in organic photovoltaic devices, because this type of structure has the ability of promoting a charge separation of the exciton generated after light absorption. This happens due to the proximity between the donor and acceptor species. In this work we have chosen the group derived from naphthalamide as electron donor, which has features like thermal and photochemical stabilities and conjugated double bonds, which cause the electrons p remain delocalized, facilitating the release of electrons when they receive energy. As electron acceptor it was chosen groups derived from fluorene,thiophene and benzonitrile containing both nitrile groups (strongly electron with drawing electron), which have characteristics of electron acceptors. The synthetic route of the NCT dyad was composed of two stages. In the first step of the synthesis of this dyad it was added a saturated chain of six carbon, proven by the NMR data with the appearance of the signs of the carbons of the chain in the region 1.5 to 3 ppm, so the next step was performed by the reaction of this product with the electron acceptor, the thiophene. In the synthetic route of the NCF it was performed three steps of the five motions initially, the first step being the same as performed for the preceding dyad. In the next step the objective of the reaction was the addition of iodine to fluorene derivative, which was confirmed by the appearance of bands of C-I bond in the IR spectra. The third and final stage of the dyad NCF had the goal of replacing the iodines by cyano group. The results show that this step it actually occurred mainly because of the nitrile band in the IR spectrum. The dyad NCB had only one step, in which the derivative naphthalamide was linked to the benzonitrile by a SN2 reaction, which was confirmed by NMR analysis that shows all the characteristic signs of the product formed. The dyad NT was the only one that did not have the separation between the donor and acceptor of electrons by a aliphatic carbon chain. Its synthesis aimed to connect the two reagents directly in only one step. All synthesized products were characterized by IR spectroscopy and 1H NMR, and the determination of their melting point, with these characterization it was concluded that only the dyad NCB was successfully obtained.